1983
DOI: 10.1071/bi9830455
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and Quantitative Changes in Milk Fat during Lactation in the Tammar Wallaby (Macro pus eugenii)

Abstract: There are major quantitative and qualitative changes in the milk lipids during lactation in the tammar wallaby, Macropus eugenii. The crude lipid content of the milk is relatively low during the first 10 weeks of lactation; between 10 and 26 weeks post partum the lipid content increases gradually but after that it increases rapidly. The triglyceride fraction of the lipid at early stages oflactation contains a large amount of palmitic acid and relatively little oleic acid whereas mature milk exhibits little pal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 12 publications
2
21
0
Order By: Relevance
“…Carbohydrate concentrations were determined as total hexose using the methods of Messer and Green (1979) and crude lipid determinations by the methods of Green et al (1983). In the first 30-35 days of lactation the quantity of milk available for collection was small making analysis for lipid difficult.…”
Section: Milk Analysesmentioning
confidence: 99%
“…Carbohydrate concentrations were determined as total hexose using the methods of Messer and Green (1979) and crude lipid determinations by the methods of Green et al (1983). In the first 30-35 days of lactation the quantity of milk available for collection was small making analysis for lipid difficult.…”
Section: Milk Analysesmentioning
confidence: 99%
“…Since the collection of milk samples analysed in this study, more recent investigations (Griffith et al 1972;Messer and Green 1979;Green et al 1980) have revealed aspects of qualitative changes in milk drawn in sequential samples from kangaroos throughout lactation. As the aim of this study was to collect over the shortest possible time sufficient milk at known stages of lactation, to permit as many assays as possible, including for the first time, assessment of the vitamin content, it was not possible to monitor in such detail changes in the composition of the milk throughout lactation.…”
Section: Discussionmentioning
confidence: 99%
“…More recent investigations have examined aspects of diverse constituents in milks from a wider range of marsupial species. For example, from among the subfamily Macropodinae, amino acids have been investigated by Renfree:et al (1982); proteins by Jordan and Morgan (1968), Bell et al (1980) and Green et al (1980); carbohydrates by Messer and Mossop (1977) and Messer and Green (1979); and lipids by Glass et al (1967), Griffiths et al (1972) and Grigor (1980). Several of these studies together with that undertaken by Lemon and Barker (1967) have followed both qualitative and quanIitative changes during lactation and, in addition, Lemon and Bailey (1966) have confirmed qualitative differences in the whey proteins of milk drawn from separate gland~ of the one animal.…”
Section: Introductionmentioning
confidence: 99%
“…The cut-off point of 185 days was used as a series of major nutritional and physiological changes occur at this age including the achievement of homeothermic control, elaboration of locomotive behaviour and changes in nutrient intake which are mainly due to changes in composition of maternal milk. 16,38,39 Experimental procedure All experiments were conducted during daylight between 09:00 and 16:00 h. Joeys were anaesthetized in a 25 L chamber with 4% halothane (Merial, Parramatta, Australia) in oxygen delivered at 5 L/min. They were intubated with the aid of a guidewire once loss of the righting reflex and absence of general body movements were achieved.…”
Section: Animalsmentioning
confidence: 99%